The Study of Quantity of Household Waste during the Coronavirus (COVID-19) Outbreak - Srijuntrapun, Patranit; Chaiboonchoe, Amphun (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The coronavirus disease (COVID-19) has not only been damaging to health, but it has also created numerous environmental issues, in particular within municipal waste management systems. This study aims to assess household waste disposal processes by looking into domestic waste management patterns and waste disposal practices in regard to everyday household waste, as well as health-care related waste (surgical masks) within a domestic setting during the Covid-19 lockdown period in Thailand. Data was gathered through an online survey conducted in Bangkok as well as five nearly provinces which were Nonthaburi, Pathumthani, Samut Songkram, Samut Prakarn and Nakorn Pathom. 438 responses were collected and under the quantitative analysis methodology, descriptive statistics (frequency, percentage, mean and standard deviation) were used to assess the data. The results of the survey show that the Covid-19 Lockdown has had an impact on an increasing number of used surgical masks and recyclable waste, however food waste has not been affected. The method of waste management selected the most is disposing all trash with general household waste. This study also presents different causes of improper waste management which are 1) the lack of an infectious waste management system in the community, leading to improper used surgical masks management; 2) slow recycle businesses during the lockdown, affecting the household waste recycling; and 3) ineffective food waste management campaigns, failing to motivate people to manage household food waste. In conclusion, each type of waste requires a unique waste management pattern which will result in appropriate and sustainable solutions during the epidemic of Coronavirus 2019 and future pandemics.